(untitled) (Swiss Medical Weekly, 2023)
T cell receptor repertoire sequencing (TCRseq) has become one of the major omic tools to study the immune system in health and disease. Multiple commercial solutions are currently available, greatly facilitating the implementation of this complex method into translational studies. However, the flexibility of these methods to react to suboptimal sample material is still limited. In a clinical research context, limited sample availability and/or unbalanced sample material can negatively impact the feasibility and quality of such analyses. We sequenced the T cell receptor repertoires of three healthy controls and four patients with GATA2 deficiency using a commercially available TCRseq kit and thereby (1) assessed the impact of suboptimal sample quality and (2) implemented a subsampling strategy to react to biased sample input quantity. Applying these strategies, we did not find significant differences in the global T cell receptor repertoire characteristics such as V and J gene usage, CDR3 junction length and repertoire diversity of GATA2-deficient patients compared with healthy control samples. Our results prove the adaptability of this TCRseq protocol to the analysis of unbalanced sample material and provide encouraging evidence for use of this method in future studies despite suboptimal patient samples.